Shigella flexneri surface protein IcsA is sufficient to direct actin-based motility. - Goldberg, M B (1995)
Shigella flexneri is a Gram-negative bacterial pathogen that can grow directly in the cytoplasm of infected host cells and uses a form of actin-based motility for intra- and intercellular spread. Moving intracellular bacteria are associated with a polarized "comet tail" composed of actin filaments. IcsA, a 120-kDa outer membrane protein necessary for actin-based motility, is located at a single pole on the surface of the organism, at the junction with the actin tail. Here, we demonstrate that stable expression of IcsA on the surface of Escherichia coli is sufficient to allow actin-dependent movement of E. coli in cytoplasmic extracts, at rates comparable to the movement of S. flexneri in infected cells. Thus, IcsA is the sole Shigella-specific factor required for actin-based motility. Continuous protein synthesis and polarized distribution of the protein are not necessary for actin tail formation or movement. Listeria monocytogenes is an unrelated bacterial pathogen that exhibits similar actin-based intracytoplasmic motility. Actin filament dynamics in the comet tails associated with the two different organisms are essentially identical, which indicates that they have independently evolved mechanisms to interact with the same components of the host cytoskeleton.